Avaliação do controle interno de estoques: um estudo de caso em uma loja comercial no Centro do estado do Rio Grande do Sul - Balbinot, Karine (2021)
This study aimed to evaluate the existence of internal control of stocks and whether these generated adequate and sufficient information in the company Gustavo Menz de Athayde – ME. In order to carry out this work, a theoretical framework was sta rted, focusing on accounting, internal controls, inventories and internal control of inventories. The methodology applied was a case study, diagnostic research, descriptive research, documental research and the approach to the problem is mixed (Quali-Quanti). Also, an interview was carried out where there was the total physical count of stocks. At the beginning of the study, there were numerous negative goods in the stock system and with the physical counting of stocks, this problem for the company was solved. At the end of this work, the goals set were achieved and it is concluded that the biggest weaknesses of the company were in the control of inputs and outputs and consequently the stock was imperfect, one of the points that impacted for this to happen was due to the pandemic.